Can we solve AI's 'trust problem'? to address users' wariness, makers of AI applications should stop overpromising, become more transparent, and consider third-party certification - Davenport, Thomas H. 1954-; Davenport, Thomas H. 1954- (MIT Sloan Management Review, 2018)
Many people don't trust decisions, answers, or recommendations from artificial intelligence. To address that problem, makers of AI applications and systems should stop overpromising, be more transparent about how systems are used, and consider third-party certification.